THE INTERPLAY OF REFLECTION AND COLLABORATION IN FLIPPED CLASSES TO NURTURE EFL PRE-SERVICE TEACHERS’ TPACK DEVELOPMENT - Elis Maolida; Anisa Sofarini; Vina Aini Salsabila (University of Kuningan, 2026)
While many studies explore the use of reflection and collaboration in supporting pre-service teachers’ learning, little is known about the integration of both strategies, particularly when tailored to foster technological pedagogical content knowledge (TPACK) development among EFL pre-service teachers. This study investigates the integration of reflection and collaboration in a flipped classroom format and examines Indonesian EFL pre-service teachers’(PSTs) perceptions of how this integration nurtures their TPACK development. Participants included a lecturer and 42 PSTs from Technology Enhanced Language Learning (TELL) class. Data were gathered through classroom observations, syllabus, and interviews with the lecturer and PSTs. The findings reveal that the lecturer facilitated PSTs’ reflection on educational technologies through a variety of reflective activities, integrated with collaborative tasks. Those intertwined practices were embraced by the PSTs and were reported to help them identify the affordances and limitations of technologies in teaching English, select suitable tools to achieve specific learning objectives, and enhance their skills in designing lessons that integrate technology, content, and appropriate teaching methods. Despite those positive perceptions, challenges such as English language barriers, diverse PST characteristics, technical issues (e.g., internet connectivity), and time constraints were identified.